Perancangan Sistem Pendukung Keputusan Pemilihan Supplier Bahan Baku pada PT. Jayatama Selaras - Nadira Iswari Narulita; Parwadi Moengin; Sucipto Adisuwiryo (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
PT. Jayatama Selaras is a manufacturer of plastic packaging in Indonesia. The problem faced by the company is the delay in the arrival of raw materials and the quality of raw materials that are not in accordance with the specifications provided by the company, so the process of returning or re-ordering needs to be carried out to new suppliers, which increases the time needed to procure raw materials. In addition, there is no integrated system in data storage that is related to the process of procuring raw materials, such as supplier data, and raw material data. The purpose of this study is to design a decision support system in providing an objective selection of alternative suppliers for the Purchasing Department of PT. Jayatama Selaras. The design of a decision support system starts with analyzing the current system using the PIECES framework. Next is creating a database using MySQL based on data management components. The next system design is designing component management models. The model used in the design of decision support systems at PT. Jayatama Selaras is AHP and TOPSIS. The last stage is designing components of dialogue management or user interfaces using the Visual Basic programming language. The results of the decision support system design show that the system can determine the best alternative suppliers, for PVC and LDPE raw materials, for LDPE raw materials to produce alternative sequences of suppliers PT. Indo Thai Trading, PT. Itochu Indonesia, PT. Tempo Nagadi Trading, PT. Kharisma Karya Plast, PT. Akino Indonesia Trading, PT. Panca Budi Pratama and PT. Unipack Plasindo. In addition, a decision support system designed to produce a database of existing suppliers and facilitate the ordering of raw materials to suppliers. The design of this decision support system is addressed to the purchasing department, production department, quality control department, and accounting department.